2004
DOI: 10.2337/diabetes.53.11.2797
|View full text |Cite
|
Sign up to set email alerts
|

Fas Deficiency Prevents Type 1 Diabetes by Inducing Hyporesponsiveness in Islet β-Cell−Reactive T-Cells

Abstract: Type 1 diabetes is an autoimmune disease wherein autoreactive T-cells promote the specific destruction of pancreatic islet ␤-cells. Evidence for a crucial role for Fas/FasL interactions in this destruction has been highly controversial because of the pleiotropic effects of Fas deficiency on the lymphoid and other systems. Fas-deficient mice are protected from spontaneous development of diabetes not because Fas has a role in the destruction of ␤-cells, but rather because insulitis is abrogated. Fas may somehow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…We found that Fas on ␤ cells played a minor role in ␤ cell death during the effector phase of diabetes, and this has been confirmed by others (13,14). In fact, the lack of infiltration into NODlpr islets may have more to do with the reduced proliferative ability of T cells, rather than a role for Fas on the islets themselves (15). Recently, better tools have been made to test the significance of Fas on ␤ cells without the complications brought about by the lpr mutation.…”
supporting
confidence: 71%
“…We found that Fas on ␤ cells played a minor role in ␤ cell death during the effector phase of diabetes, and this has been confirmed by others (13,14). In fact, the lack of infiltration into NODlpr islets may have more to do with the reduced proliferative ability of T cells, rather than a role for Fas on the islets themselves (15). Recently, better tools have been made to test the significance of Fas on ␤ cells without the complications brought about by the lpr mutation.…”
supporting
confidence: 71%
“…Although the analysis of the fas pathway in NOD mice was complicated by the abnormal immune phenotype observed in lpr mice, alternative models convincingly demonstrated a role for the fas-fas ligand pathway in autoimmune diabetes (26,50). Thus, it was surprising that perforin and fas deficiency were not necessary for tissue damage in NOD-B7-2KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although blocking IFN-␥ by mAbs reduced the incidence of diabetes in NOD mice (54), NOD-IFN-␥KO mice develop diabetes with incidence similar to NOD mice and only slightly delayed kinetics (23,24). In contrast, whereas fas and perforin are involved in the development of autoimmune diabetes and islet destruction in NOD mice (21,22,26,50), both pathways were dispensable for autoimmune neuropathy. These results suggest that although both diabetes and neuropathy are T cell-mediated inflammatory autoimmune diseases occurring on the autoimmune-prone NOD background, the immune mechanisms underlying these diseases are distinct.…”
Section: Discussionmentioning
confidence: 99%
“…Fas was initially thought to be critical in ␤-cell apoptosis in type 1 diabetes since NOD mice homozygous for the lpr mutation were protected from diabetes development (5,12). However, this is most likely a result of their dysregulated immune system from the lpr mutation rather than the role of Fas in ␤-cell destruction per se (34). In keeping with this notion, NOD-lpr/lpr islets transplanted into normal female NOD mice did not give protection from diabetes development (1).…”
Section: Fasmentioning
confidence: 99%